Reflextions on itinerant education on EJA: report of a specialist teacher - Annie Gomes Redig (Universidade Federal de Santa Maria (UFSM), 2010)
This paper has the objective to analyse and reflect on the performance of the itinerant teacher who works with students with intellectual disabilities at Education of young and adults. The present research used qualitative methodology with a semi-structured interview with the only itinerant teacher who works with EJA in that neighborhood. And it was developed at a municipal school at Rio de Janeiro, in the first semester of 2009. It was observed that both the regular and the special teachers show resistence to the special students and are not prepared to teach them. After this, we can conclude that there still is a lot of resistence to these students in regular classes, but the presence of this professional makes the job a lot easier.